Conductas sexuales de riesgo en estudiantes universitarios - Pacompia, Mery (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
Risky sexual behavior is the exposure of the individual to sexual practices that increase the risk of acquiring or spreading sexually transmitted diseases, such as the dreaded HIV/AIDS and unwanted pregnancies. Among these practices are: sexual initiation at an early age, sex without the use of a condom, having multiple sexual partners, having sex under the influence of alcohol or other drugs, and having had a previous STI. The present research work was carried out with the objective of determining the sexual risk behaviors in students of the National University of the Puno Altiplano. The type of study was descriptive, with a non-experimental cross-sectional design; the population was made up of 413 students and the sample of 199 from the Biomedical, Social and Engineering academic areas; selected through non-probabilistic convenience sampling. The technique was the survey and as a research instrument the Index of Risky Sexual Behavior (ICSR), by Moral J and Garza D, duly validated and reliable. The results show that 55.8% of students are not sexually active, while 42.2% are. 40.9% present medium risk, followed by 36.4% high risk and 22.7% low risk. According to academic areas, 17.7% of the biomedical area presents medium-risk sexual behaviors; on the other hand, 12.5% ​​of social and 15.9% of engineering have a higher prevalence of high-risk sexual behaviors. According to indicators, the risky sexual behaviors most practiced by sexually active students are: multiple sexual partners, occasional sexual encounters, unprotected sexual relations, recurrence of pregnancy tests, with the majority of those surveyed being those who did not undergo the test to rule out STIs, reaching the conclusion that the students of the first cycles, in a relative majority, present sexual behaviors of medium and high risk.